PRAGMATIC FEATURES OF WORD STRUCTURE IN UZBEK AND ENGLISH LANGUAGES - Abdurazzoqova Sevara (Bright Mind Publishing, 2025)
This article presents a comprehensive comparative analysis of the pragmatic features of word structure in the Uzbek and English languages. It explores the processes of word formation and the pragmatic functions embedded within morphological components, with a focus on how context influences semantic and stylistic interpretations. The study particularly examines the role of affixes in shaping pragmatic meanings and their impact on the degree, tone, and clarity of information conveyed during communication. Through detailed linguistic analysis, the research identifies both similarities and distinctive differences in the pragmatic strategies employed by each language. Furthermore, it discusses the communicative functions of these strategies within various discourse contexts, highlighting their significance in facilitating effective interaction. The findings offer new insights into the morphological and lexical frameworks of Uzbek and English, emphasizing their implications for applied linguistics fields such as translation, language teaching, and intercultural communication. This research contributes to a deeper understanding of how pragmatic factors influence word structure and enrich the communicative potential of language.